Multi-trait analysis of domestication genes in Cicer arietinum – Cicer reticulatum hybrids with a multidimensional approach: Modeling wide crosses for crop improvement. (August 2019) - Shin, Min-Gyoung; Bulyntsev, Sergey V.; Chang, Peter L.; Korbu, Lijalem Balcha; Carrasquila-Garcia, Noelia; Vishnyakova, Margarita A.; Samsonova, Maria G.; Cook, Douglas R.; Nuzhdin, Sergey V.
Highlights: Two wild chickpea species were crossed with the elite, early flowering C. arietinum cultivar ICCV96029. Single-trait QTLs and multi-trait QTLs were found using mixed model-based association analyses. Bayesian analysis identified inter-trait relationships controlling the duration of vegetative growth and seed maturation. Random Forest was used to identify traits most characteristic of wild species origin. Abstract: Domestication and subsequent breeding have eroded genetic diversity in the modern chickpea crop by ˜100-fold. Corresponding reductions to trait variation create the need, and an opportunity, to identify and harness the genetic capacity of wild species for crop improvement. Here we analyze trait segregation in a series of wild x cultivated hybrid populations to delineate the genetic underpinnings of domestication traits. Two species of wild chickpea, C. reticulatum and C. echinospermum, were crossed with the elite, early flowering C. arietinum cultivar ICCV96029. KASP genotyping of F2 parents with an FT-linked molecular marker enabled selection of 284 F3 families with reduced phenological variation: 255 F3 families of C. arietinum x reticulatum (AR) derived from 17 diverse wild parents and 29 F3 families of C. arietinum x echinospermum (AE) from 3 wild parents. The combined 284 lineages were genotyped using a genotyping-by-sequencing strategy and phenotyped for agronomic traits. 50 QTLs in 11 traits were detected from AR and 35 QTLs in 10 traits from the combined data. Using hierarchical clustering to assign traits to six correlated groups and mixed model based multi-trait mapping, four pleiotropic loci were identified. Bayesian analysis further identified four inter-trait relationships controlling the duration of vegetative growth and seed maturation, for which the underlying pleiotropic genes were mapped. A random forest approach was used to explore the most extreme trait differences between AR and AE progenies, identifying traits most characteristic of wild species origin. Knowledge of the genomic basis of traits that segregate in wild-cultivated hybrid populations will facilitate chickpea improvement by linking genetic and phenotypic variation in a quantitative genetic framework.